2021
DOI: 10.3390/ijerph18073498
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the EWGSOP2 Cut-Points of Low Grip Strength for Identifying Sarcopenia and Frailty Phenotype: A Cross-Sectional Study in Older Inpatients

Abstract: Background: The European Working Group on Sarcopenia has recently proposed revised cut-off values for the definition of low grip strength (EWGSOP2). We therefore compared performance of the EWGSOP2 cut-off definition of low grip strength with other internationally used cut-off points in a sample of older patients. Methods: We analyzed geriatric assessment data in a cross-sectional sample of 98 older patients admitted to a post-acute care hospital. First, we compared prevalence of sarcopenia and frailty phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
1
22
1
Order By: Relevance
“…Reis et al [ 34 ] were among the first to analyze the consequences of applying the new EWGSOP2 guideline instead of the former EWGSOP1 for sarcopenia case finding in older geriatric inpatients and described a substantial mismatch with a significant lowering of the number of men diagnosed with sarcopenia. The discord in prevalence from the lower numbers of the EWGSOP2 have been further explored and reported by other studies [ 35 , 36 , 37 , 39 , 40 , 41 ]. Besides the several distinguished differences between the two versions (lowering the diagnostic thresholds for isometric handgrip strength and muscle mass, the introduction of new suggested measurement methods for muscle strength, etc.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Reis et al [ 34 ] were among the first to analyze the consequences of applying the new EWGSOP2 guideline instead of the former EWGSOP1 for sarcopenia case finding in older geriatric inpatients and described a substantial mismatch with a significant lowering of the number of men diagnosed with sarcopenia. The discord in prevalence from the lower numbers of the EWGSOP2 have been further explored and reported by other studies [ 35 , 36 , 37 , 39 , 40 , 41 ]. Besides the several distinguished differences between the two versions (lowering the diagnostic thresholds for isometric handgrip strength and muscle mass, the introduction of new suggested measurement methods for muscle strength, etc.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, it has been suggested that until this global consensus is reached, prevalence data should be reported and interpreted within its own context [ 33 ]. Upon the publication of the revised EWGSOP2 consensus criteria [ 3 ], potentially different outcomes when comparing previous criteria have been investigated [ 34 , 35 , 36 , 37 , 38 , 39 ]. Reis et al [ 34 ] were among the first to analyze the consequences of applying the new EWGSOP2 guideline instead of the former EWGSOP1 for sarcopenia case finding in older geriatric inpatients and described a substantial mismatch with a significant lowering of the number of men diagnosed with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to our study, low strength was characterized as having low grip strength or chair rise speed in the EWGSOP2 definition; this would result in a higher prevalence compared with the use of grip strength alone as a measure of strength. Prevalence of low grip strength using various thresholds was compared in a study comprising 98 men and women admitted to a geriatric rehabilitation hospital in Switzerland 28 . As expected, prevalence of low grip strength according to the EWGSOP2 threshold (10.2%) was considerably lower compared with the SDOC threshold (19.4%).…”
Section: Discussionmentioning
confidence: 72%
“…The suggested use of muscle weakness or walking slowness for the identification of sarcopenia [ 22 , 50 , 54 ] raises the question of the possibility of agreement between the two for diagnosis, although the correlation appears to be weak between the values of these two criteria [ 55 ].…”
Section: Discussionmentioning
confidence: 99%